Economic regulation, opportunity-driven entrepreneurship and gender gap: emerging versus high income economies. - Bárcena-Martín, Elena María; Medina-Claros, Samuel; Pérez-Moreno, Salvador Jesús (SAGE, 2021)
Purpose – Institutional environment plays a crucial role in determining the nature of entrepreneurship that prevails in an economy. In this paper, we address how business, labour and credit regulations contribute differently to both the overall prevalence of opportunity-driven entrepreneurship and its gender gap in high-income and emerging economies. Design/methodology/approach – On the basis of an unbalanced panel of 41 countries over the period 2005-2016, we estimate system Generalized Method of Moments models. We also perform an Ordinary Least Square analysis to address gender differences in opportunity-driven entrepreneurship. Findings – We find that higher credit market liberalisation is especially associated with more entrepreneurship by opportunity. Nevertheless, while credit market regulation stands out as a key element to promote opportunity-based entrepreneurship in both high-income and emerging countries, in the emerging world business regulation is also largely related to the prevalence of opportunity entrepreneurship. In terms of gender gap, business and labour market freedom seem to exert an equalizing effect on the divide in entrepreneurship by opportunity, specifically in emerging economies. Originality/value – Our findings allow the identification of regulatory policy reform priorities to enhance the prevalence of opportunity-driven entrepreneurship depending on the level of a country’s development. They also identify which specific areas of economic regulation would speed up closing the gender gap in opportunity entrepreneurship.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/2724
International Journal of Entrepreneurial Behavior & Research Vol. 27 No. 5, 2021 pp. 1311-1328 © Emerald Publishing Limited 1355-2554 DOI 10.1108/IJEBR-05-2020-0321
Keywords: Emprendedores; Empresarias; Mujeres en el desarrollo; Sexismo; Entrepreneurship; Opportunity; Gender introduction; Regulation